Deference and Defiance in Nineteenth-Century Japan - Kelly, William W. (William Wright), 1946- (Book collections on Project MUSE., 1985)
Four times in the nineteenth century, popular protest movements spread across the northern Japanese rice plain of Shonai. This study skillfully portrays the changing character of the protests, their relationship to one another, and their role in the societal transformation of Shonai first during Japan's shift from tributary polity to nation state and then from mercantilism to capitalism.Originally published in 1985.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.